Fermentado alcoólico acidificado de cajuína, tipo sidra, como proposta de aproveitamento do pedúnculo de caju - Machado Matias, Fernando (2024)
The cashew tree is a plant native to Brazil and significantly impacts the agroindustry of the Northern states. One of the problems with this culture is the waste of the accessory fruit, the cashew apple, due to its high perishability. Within this scenario, this study proposes a new product: the fermentation of the cashew apple clarified juice. Therefore four formulations, fermented by the yeast Lachancea spp., a non-saccharomyces yeast, were developed. The formulations had fermented at 23 °C, stabilized, and divided according to the residual sugar content and the form of carbonation: SCN (Dry Natural Carbonated); MSCN (Semi-Dry Natural Carbonated); SCF (Dry Forced Carbonation); MSCF (Semi-Dry Forced Carbonation). The experiments happened in laboratorial scale. The formulations were characterized and analyzed for centesimal composition, pH 3,56±0,01 to 3,66±0,01, soluble solids 1,91±0,00 to 3,42±0,08°Brix, alcohol content 4,78±0,20 to 5,03±0,32%, ashes 0,28±0,45 to 0,34±3,66%, and dry extract 1,94±0,04 a 30,8±0,03%. Besides they were also analyzed for phenolic compounds 109,92±6,86 to 123,68±1,34, total acidity 115,33±1,16 to 129,33±3,01 and volatile acidity 16,22±0,7 to 19,27±3,22. All the formulations results were in the cashew apple legislation parameters, by the standards evaluated in this study. Afterwards a Nuclear Magnetic Resonance (MNR) analysis for the main compounds, which demonstrated a high complexity of organic acids, such as lactic, citric, malic, succinic, and gamma-aminobutyric, also a noticeable quantity of anacardic acid was preserved. At last, a sensory analysis followed. The focal group selected seven descriptive terms and highlighted the cashew-apple aroma. For the acceptance tests all the samples had a positive acceptability, varying between 6,20±1,72 to 6,67±1,74, and the semi-dry with forced carbonation was selected as the favorite and had the highest buying intention. In the CATA test the participants noticed a significant difference in carbonation, 99% and 100% for the forced carbonated samples, and an intense aroma for the natural carbonated samples. In conclusion, the clarified cashew-apple juice proves to be a suitable wort to produce alcoholic beverages, and the practicability of the Lachancea spp. yeast. The resulting beverage is an enormous potential of pairing with the culinary of Ceara, highly refreshing, and a possibility of usage in mixology.